Sociodemographic and dietary profile of 4,471 childbearing-age women planning a pregnancy - Marta Cuervo; Leticia Goni; Susana Santiago; Itziar Zazpe; Aquilino García; J. Alfredo Martínez (Nutrición Hospitalaria, 2014)
Background: The maintenance of healthy lifestyles is of great importance to prevent pregnancy-related diseases at early stages. For this reason, the knowledge of the overall wellbeing of women at childbearing-age is necessary to provide appropriate advice to maintain or improve the nutritional status. The aim of this research was to assess the lifestyles of childbearing-age women planning a pregnancy and to examine the difference between primiparae and multiparae women on these lifestyles. Methods: This cross-sectional survey involved 4,471 Spanish women at childbearing-age that were planning a pregnancy. Information was collected through a questionnaire by community health professionals. Results: The profile of childbearing-age recruited women planning a pregnancy were in her early thirties (31.4 ± 4.8 years) and 72.5% were seeking for her first baby. They had a good self-perception of their nutritional and health status and followed a balanced diet. Interestingly, primiparae women had lower risk of health complications but they were greater consumers of tobacco and alcohol (p < 0.001), and consumed less fortified milk, iodine and iron supplements than multiparae women. Additionally, the examined population showed a more sedentary pattern in primiparae women as compared to the remaining group concerning hours/day lying, sitting and standing. Conclusion: Differences between both preconceptional conditions (primiparae and multiparae women) bring a great opportunity to promote healthy habits among childbearing-aged women, according to the personal profile, in order to prevent burdens in future pregnancies underlying modifiable or preventable factors.